Problem in the surgical correction of long-face with vertical open bite - Coen Pramono D (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Long-face cases usually need both treatment of orthodontic and surgery. The problem appearing in the correction of long-face might be able to be related with some difficult factors such as the crowded teeth and excessive vertical height. A class III malocclusion and excessive open bite can be also followed in long face. This situation might worsen the facial aesthetic condition and increase the difficulty in orthodontic treatment. The orthodontic approach is oriented toward positioning the teeth pre-surgically to facilitate the surgical plan. The form of mandible which has grown in the downward direction in the area of mandible angle makes an extreme vertical open bite. The maxilla is usually presented with a maxillary hypolasia. Double-jaw surgery was done as the correction of the lower jaw alone would produce a flattened face appearance and difficulty in repositioning the mandible to achieve a good facial performance. Several cephalometric points were measured to observe the facial situation progress after surgery. Two cases of longface are reported, and the same surgical treatments were performed and showed different results.